2021
DOI: 10.3390/antibiotics10111381
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ursolic and Oleanolic Acids on Lipid Membranes: Studies on MRSA and Models of Membranes

Abstract: Staphylococcus aureus is an opportunistic pathogen and the major causative agent of life-threatening hospital- and community-acquired infections. A combination of antibiotics could be an opportunity to address the widespread emergence of antibiotic-resistant strains, including Methicillin-Resistant S. aureus (MRSA). We here investigated the potential synergy between ampicillin and plant-derived antibiotics (pentacyclic triterpenes, ursolic acid (UA) and oleanolic acid (OA)) towards MRSA (ATCC33591 and COL) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 75 publications
(107 reference statements)
0
10
0
Order By: Relevance
“…The potential synergy between ampicillin and plant antibiotics (pentacyclic triterpenes, ursolic acid (UA) and oleanolic acid (OA)) against MRSA (ATCC33591 and COL) and the mechanisms involved were studied by Verstraeten S. et al [ 4 ]. They monitored the fluorescence of Bodipy-TR-Cadaverin, propidium iodide, and membrane-potential-sensitive probes to determine the ability of UA and OA to bind to lipoteichoic acids (LTAs) and induce membrane permeabilization and depolarization, respectively.…”
mentioning
confidence: 99%
“…The potential synergy between ampicillin and plant antibiotics (pentacyclic triterpenes, ursolic acid (UA) and oleanolic acid (OA)) against MRSA (ATCC33591 and COL) and the mechanisms involved were studied by Verstraeten S. et al [ 4 ]. They monitored the fluorescence of Bodipy-TR-Cadaverin, propidium iodide, and membrane-potential-sensitive probes to determine the ability of UA and OA to bind to lipoteichoic acids (LTAs) and induce membrane permeabilization and depolarization, respectively.…”
mentioning
confidence: 99%
“…TCA cycle activity and amino acid catabolism may also reflect the potential turnover of membrane lipids in response to the increased production of STX, as this process requires a significant amount of energy. Furthermore, previous research on other pentacyclic triterpenes (i.e., ursolic acid and oleanolic acid) has shown that incorporation of these molecules into cellular membranes changes membrane fluidity and leads to increased membrane rigidity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on other triterpenes have found that their antibacterial activity is specific to Gram-positive microorganisms [ 41 , 42 , 45 ], including biofilm inhibition and reduction [ 46 , 47 ]. Despite GRA lacking bactericidal activity against MRSA biofilms, it is effective at reducing bacterial bioburden in two different biofilm models, suggesting that even at sub-lethal doses, GRA is potentially useful as a biofilm dispersal agent.…”
Section: Discussionmentioning
confidence: 99%
“…Laurdan GP was calculated based on previous studies. 36 Membrane Permeability Assay. E. faecalis OG1RF overnight cultures were diluted 200-fold (1 × 10 7 CFU) and incubated with HEPES medium.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%